Generation of Tasseled Cap Transformation Coefficients for the Use of TiungSAT-1 Multi Spectral Earth Imaging System (MSEIS) Data - Kanniah, Kasturi Devi; Teh, Poey Lee (Astronautic Technology (M) Sdn. Bhd., 2003)
The so-called â€œTasseled Capâ€ transformation developed by Kauth and Thomas in 1976 is a means for highlighting the most important (spectrally-observable) phenomena of crop development in a way that allows discrimination of specific crops. For Landsat Multispectral Scanner (MSS) data, the Tasseled cap transform perform an orthogonal transformation of the original data into new four-dimensional space consisting of the soil brightness index (SBI), the green vegetation index (GVI), the yellow stuff/vegetation index (YVI) and non-such index (NSI) associated with atmospheric effects. For LandSAT Thematic Mapper (TM) data, the Tasseled Cap vegetation index consists of three factors, â€œBrightnessâ€, â€œGreennessâ€, and â€œThirdâ€. The Brightness and Greenness are equivalent to the MSS tasseled cap SBI and GVI, and the third component is related to soil features, including moisture status. In this project, an effort has been made to generate Tasseled Cap coefficient for TiungSAT-1 Multi Spectral Earth Imaging System (MSEIS) data which has no such coefficient yet. This is a recent effort since TiungSAT-1 is a Malaysian micro satellite which was recently launched in September 2000. These generated coefficients were then used to generate TC layers to derive vegetation and soil information from TiungSAT-1 data. Besides TiungSAT-1 data, LandSAT TM data were also used to compare the results obtained from TiungSAT-1. Both TiungSAT-1 and TM images were processed for TTC and supervised classification. The results show that the generated TTC coefficients are sufficient to separate vegetation information from TiungSTA-1 data.